An in vivo genome‐wide shRNA screen identifies BCL6 as a targetable biomarker of paclitaxel resistance in breast cancer. Issue 8 (18th May 2021) - Sultan, Mohammad; Nearing, Jacob T.; Brown, Justin M.; Huynh, Thomas T.; Cruickshank, Brianne M.; Lamoureaux, Emily; Vidovic, Dejan; Dahn, Margaret L.; Fernando, Wasundara; Coyle, Krysta M.; Giacomantonio, Carman A.; Langille, Morgan G.I.; et al.
Abstract : Paclitaxel is a common breast cancer drug; however, some tumors are resistant. The identification of biomarkers for paclitaxel resistance or sensitivity would enable the development of strategies to improve treatment efficacy. A genome‐wide in vivo shRNA screen was performed on paclitaxel‐treated mice with MDA‐MB‐231 tumors to identify genes associated with paclitaxel sensitivity or resistance. Gene expression of the top screen hits was associated with tumor response (resistance or sensitivity) among patients who received neoadjuvant chemotherapy containing paclitaxel. We focused our validation on screen hit B‐cell lymphoma 6 (BCL6), which is a therapeutic target in cancer but for which no effects on drug response have been reported. Knockdown of BCL6 resulted in increased tumor regression in mice treated with paclitaxel. Similarly, inhibiting BCL6 using a small molecule inhibitor enhanced paclitaxel treatment efficacy both in vitro and in vivo in breast cancer models. Mechanism studies revealed that reduced BCL6 enhances the efficacy of paclitaxel by inducing sustained G1/S arrest, concurrent with increased apoptosis and expression of target gene cyclin‐dependent kinase inhibitor 1A. In summary, the genome‐wide shRNA knockdown screen has identified BCL6 as a potential targetable resistance biomarker of paclitaxel response in breast cancer. Abstract : An in vivo genome‐wide shRNA screen identified several potential biomarkers of paclitaxel response in breast cancer, including transcriptional repressor BCL6 as a biomarker of paclitaxel resistance. Inhibition of BCL6 in breast cancer cells and tumors resulted in increased response to paclitaxel. Paclitaxel with BCL6 inhibition resulted in increased expression of BCL6 target gene CDKN1A, sustained G1/S arrest, and increased apoptosis.